High-energy diet does not overcome the negative impact of conjugated linoleic acid on young broiler performance - katia Maria cardinal; Júlia Guazzelli Pezzali; Lucas de Marques Vilella; Priscila de Oliveira Moraes; Andréa Machado Leal Ribeiro (Acta Scientiarum. Animal Sciences, 2020)
The aim of this study was to evaluate the effect of conjugated linoleic acid (CLA) supplementation in diets with different energy levels in broiler performance. Birds were offered a starter (1-21 d), grower (22-35 d) and finisher (36-42 d) diets; wherein soybean oil was replaced by CLA. The study consisted of a 3 × 2 factorial arrangement with two CLA levels (0 and 1%) and three energy levels (3050, 3100 and 3150 ME kg-1 diet). During the grower and finisher periods, birds were fed diets with same energy level and CLA supplementation was maintained the same. Growth performance was assessed weekly, and carcass and cuts yield were assessed at 42d. Interaction effect of CLA by energy level was observed in broiler performance and carcass yield throughout the study (p > 0.05). During the overall period (1-42 d) broiler performance was not affected by CLA (p > 0.05).However, CLA supplementation (1%) decreased weight gain (p < 0.05) at 21d, regardless of energy level, with no effects on feed intake and feed conversation rate (p > 0.05). The increase in dietary energy was not able to compensate the negative effect on growth performance of broilers supplemented with 1% CLA at the starter period.